한국판 Alexian Brothers Urge to Self-Injure Scale (ABUSI-K) 척도의 예비 타당화 연구 - 김민경(Min-kyeong Kim); 현명호(Myoung-Ho Hyun); 이서정(Seo Jeong Lee) (Seuteureseu yeon-gu (Online), 2023)
본 연구의 목적은 자살의도 없는 자해 충동을 측정하는 Alexian-Brothers Urge to Self-Injure Scale (ABUSI)을 한국어 척도로 타당화하고자 함에 있다. 3년 이내의 자살의도 없는 자해 경험이 있는 성인 남녀 표본 389명에서 한국판 ABUSI (ABUSI-K)의 내적합치도가 높았으며, 자해 충동을 측정하는 단일 요인의 척도임을 확인하였다. 본 척도에서 부정긴급성, 자기비판/자기공격과 자기위안, 자해 사고 및 행동 질문지의 자해 모듈, 우울 및 불안과의 수렴타당도는 안정적이었다. 척도를 통해 자살의도 없는 자해와 그 충동에 대해 다면적으로 이해할 수 있을 것이며, 임상적 개입에 있어서도 유용할 것으로 기대한다. Background: This study aimed to validate the Korean version of the Alexian-Brothers Urge to Self-injure Scale (ABUSI) for measuring non-suicidal self-injury urges. Methods: Analysis was conducted on a sample of 389 adult men and women who had inflicted self-harm without suicidal intent within three years. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was conducted to confirm the single factor of the scale, and convergent validity was assessed to establish the relationship between ABUSI-K and Negative Urgency (UPPS-P), Self-Criticism/Attacking and Reassurance (FSCRS), and Self-Injurious Thoughts and Behaviors Interview (SITBI). Results: The Korean version of the Alexian-Brothers Urge to Self-Injure Scale (ABUSI-K) showed high internal consistency and, like the original scale, was confirmed to be a single-factor scale measuring the urge to self-injure. Convergent validity with negative urgency, self-criticism/self-attacking and selfreassuring, the NSSI module of self-injurious thoughts and behaviors, and depression and anxiety were also significant, indicating that ABUSI-K’s psychometric benefits are confirmed. Conclusions: The results of this study will provide a multifaceted understanding of self-injury without suicidal intent and the urges that occur before self-injury. They are expected to be useful in clinical interventions for individuals who have engaged in non-suicidal self-injuries. KCI Citation Count: 0